Concerns of Women Choosing Community Birth During the COVID‐19 Pandemic: A Qualitative Study. (1st October 2021) - DeJoy, Sharon Bernecki; Mandel, Deborah; McFadden, Niamh; Petrecca, Lauren
Abstract : Introduction: During the coronavirus disease 2019 (COVID‐19) pandemic, midwives have reported increased demand for community birth services. The purpose of this qualitative study was to understand childbearing persons' decision‐making during the pandemic and to illuminate their experiences giving birth in community settings. Methods: The study was framed by the interpretive phenomenological approach. Eligible participants were recruited from midwives providing out‐of‐hospital birth services. Of the 26 women who agreed to an interview, 17 were able to be reached and interviewed. Interviews followed a semistructured guide. Early paradigm cases were coded by all researchers, and then the first author coded the remaining transcripts. The final thematic structure was developed by the research team through an iterative process and validated through member checking. Results: Four themes were identified: prior desire for a community birth, perceived susceptibility, barriers to choice, and isolation. Discussion: Many participants had a preexisting desire for community birth and used the pandemic to justify their choice. However, birth options were often limited by finances and geography. Attitude toward COVID‐19 varied by knowledge and experience. Many participants experienced stress and isolation.